1999
DOI: 10.1097/00007890-199907270-00011
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral Transplantation for Megacystis Microcolon Intestinal Hypoperistalsis Syndrome

Abstract: This is the first report in the literature of multivisceral transplantation for MMIHS. Although one of the three patients died 44 days after surgery from multiorgan system failure, the other two patients had long-term survival after transplant and both grew well on enteral feeding alone. One patient died 17 months from a non-transplant-related complication, while the other is living at home off of TPN, with almost complete dietary rehabilitation 17 months after transplant. Our case reports suggest that multivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…[1][2][3][4][5][6] Childhood diseases that cause intestinal failure include short gut syndrome due to congenital anomalies (e.g., gastroschisis, jejunal atresia), necrotizing enterocolitis (NEC), and midgut volvulus. Other diseases include functional abnormalities such as megacystis-microcolon syndrome, 7 Hirschsprung's disease, and microvillus inclusion disease. 8 Due to the early onset of these childhood causes of intestinal failure, patients often patients as well as to provide a comprehensive analysis of prognostic factors.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Childhood diseases that cause intestinal failure include short gut syndrome due to congenital anomalies (e.g., gastroschisis, jejunal atresia), necrotizing enterocolitis (NEC), and midgut volvulus. Other diseases include functional abnormalities such as megacystis-microcolon syndrome, 7 Hirschsprung's disease, and microvillus inclusion disease. 8 Due to the early onset of these childhood causes of intestinal failure, patients often patients as well as to provide a comprehensive analysis of prognostic factors.…”
mentioning
confidence: 99%
“…Multivisceral and IT are currently the only therapeutic option that would allow these patients to start oral feedings without other complications. We and others [5,16,17] have demonstrated that MVT can be accomplished with good results in MMIHS-or CIPOaffected patients who have TPN-induced liver failure. This subset of patients represents about 10% of the IT recipients in our institution.…”
Section: Discussionmentioning
confidence: 77%
“…We herein describe our experience with patients who had ITs or multivisceral transplants (MVTs) owing to GID syndromes, excluding those with Hirschsprung disease. Three of these patients with MMIHS have been previously reported [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multivisceral transplantation for MMIHS was first described in 1999 [22], and to date, thirteen cases of transplantation have been reported, in which one had received isolated intestinal transplantation and twelve were multivisceral [20]. It is generally accepted that transplantation is an alternative and long-term option for children who cannot tolerate total parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%